Validity of ICD‐10‐CM diagnoses to identify hospitalizations for serious infections among patients treated with biologic therapies. Issue 7 (3rd May 2021) - Lo Re, Vincent; Carbonari, Dena M.; Jacob, Jerry; Short, William R.; Leonard, Charles E.; Lyons, Jennifer G.; Kennedy, Adee; Damon, Jolene; Haug, Nicole; Zhou, Esther H.; Graham, David J.; McMahill‐Walraven, Cheryl N.; et al.
Abstract: Purpose: Identifying hospitalizations for serious infections among patients dispensed biologic therapies within healthcare databases is important for post‐marketing surveillance of these drugs. We determined the positive predictive value (PPV) of an ICD‐10‐CM‐based diagnostic coding algorithm to identify hospitalization for serious infection among patients dispensed biologic therapy within the FDA's Sentinel Distributed Database. Methods: We identified health plan members who met the following algorithm criteria: (1) hospital ICD‐10‐CM discharge diagnosis of serious infection between July 1, 2016 and August 31, 2018; (2) either outpatient/emergency department infection diagnosis or outpatient antimicrobial treatment within 7 days prior to hospitalization; (3) inflammatory bowel disease, psoriasis, or rheumatological diagnosis within 1 year prior to hospitalization, and (4) were dispensed outpatient biologic therapy within 90 days prior to admission. Medical records were reviewed by infectious disease clinicians to adjudicate hospitalizations for serious infection. The PPV (95% confidence interval [CI]) for confirmed events was determined after further weighting by the prevalence of the type of serious infection in the database. Results: Among 223 selected health plan members who met the algorithm, 209 (93.7% [95% CI, 90.1%–96.9%]) were confirmed to have a hospitalization for serious infection. After weighting by the prevalence of the type of serious infection, the PPV of the ICD‐10‐CM algorithm identifying a hospitalization for serious infection was 80.2% (95% CI, 75.3%–84.7%). Conclusions: The ICD‐10‐CM‐based algorithm for hospitalization for serious infection among patients dispensed biologic therapies within the Sentinel Distributed Database had 80% PPV for confirmed events and could be considered for use within pharmacoepidemiologic studies.